2010
DOI: 10.1094/pdis-94-1-0109
|View full text |Cite
|
Sign up to set email alerts
|

A Polymerase Chain Reaction Assay for the Detection ofXanthomonas campestrispv.musacearumin Banana

Abstract: Polymerase chain reaction (PCR) primers (BXW-1 and BXW-3) for conventional PCR were developed from conserved sequences in the hrpB operon of the hrp gene cluster from Xanthomonas campestris pv. musacearum, the causative agent of banana Xanthomonas wilt (BXW). All 50 strains of X. campestris pv. musacearum, isolated from Uganda, Rwanda, and Tanzania, produced a 214-bp amplicon when whole cells, bacterial ooze from infected tissue, and genomic DNA purified from bacterial ooze or infected tissue were used as temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 43 publications
0
21
1
Order By: Relevance
“…An alternative approach, amenable to the rapid detection and identification of bacterial plant pathogens is the use of the polymerase chain reaction (PCR). A specific assay for detecting Xcm has recently been proposed based on PCR amplification of the hrpB gene [22]. However, this gene is also conserved in Xvv and this assay was unable to distinguish between Xcm and non-banana-pathogenic isolates Xvv NCPPB702 and NCPPB1326 [22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…An alternative approach, amenable to the rapid detection and identification of bacterial plant pathogens is the use of the polymerase chain reaction (PCR). A specific assay for detecting Xcm has recently been proposed based on PCR amplification of the hrpB gene [22]. However, this gene is also conserved in Xvv and this assay was unable to distinguish between Xcm and non-banana-pathogenic isolates Xvv NCPPB702 and NCPPB1326 [22].…”
Section: Resultsmentioning
confidence: 99%
“…A specific assay for detecting Xcm has recently been proposed based on PCR amplification of the hrpB gene [22]. However, this gene is also conserved in Xvv and this assay was unable to distinguish between Xcm and non-banana-pathogenic isolates Xvv NCPPB702 and NCPPB1326 [22]. Another study [23] generated several PCR primer pairs that were highly specific for Xcm but this study did not utilize Xcm or Xvv genomic sequence but rather used sequences from a range of other xanthomonads and so the candidate primers had to be tested for specificity by trial and error.…”
Section: Resultsmentioning
confidence: 99%
“…Several molecular markers, such as Rep‐PCR (Aritua et al ., ), random amplification of polymorphic DNAs (RAPDs) (Odipio et al ., ), enterobacterial repetitive intergenic consensus‐PCR (ERIC‐PCR) (Lewis‐Ivey et al ., ) and single‐nucleotide polymorphisms (SNPs) (Wasukira et al ., ), have been developed to study Xcm populations. These molecular fingerprinting methods concluded that Xcm strains are monomorphic.…”
Section: Genetic Diversity Of Xcmmentioning
confidence: 99%
“…In addition, culture-based techniques are prone to give false negative results when used to assess latently infected plants due to the low bacterial load (Mwangi, 2007;Tripathi et al, 2007). Recent developed molecular approaches, that is, (Polymerase chain reaction) PCR need only slight amount of DNA for detection, however they are often costly, time consuming, and require tissue or DNA samples to be transported to the laboratory (Aritua et al, 2008;Lewis Ivey et al, 2010;Adikini et al, 2011;Adriko et al, 2011).…”
Section: Introductionmentioning
confidence: 99%